2004
DOI: 10.1063/1.1707204
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Nd3+ ions in oxyfluoride glasses and glass ceramics comparing different preparation methods

Abstract: A study of optical properties of Nd3+ doped oxyfluoride glasses and glass ceramics prepared by three different methods has been carried out. These methods start from NdF3, Nd2O3, or a Nd3+ ion solution as doping agent. The alternative preparation method based on a preliminary dissolution of the Nd3+ ions is proposed in order to avoid nonhomogeneous dopant distribution and spontaneous devitrification during glass elaboration. In the frame of the Judd–Ofelt theory, main radiative parameters have been studied: tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 43 publications
2
34
1
Order By: Relevance
“…The literature shows that NdF 3 based samples present an increase in transitions from glass to glass ceramics, which implies an improvement in mechanical properties [31]. In this study, Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The literature shows that NdF 3 based samples present an increase in transitions from glass to glass ceramics, which implies an improvement in mechanical properties [31]. In this study, Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Jacobs and Weber [32] [31]. The values obtained from glass and glass ceramic samples considered in this study are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter 6 is known to be proportional with the rigidity of host glass. 16 The slight decrease of 6 from TZF5 to TZF30 indicates the lessening mechanical properties of glass samples. As for the value of 4 / 6 , it is observed to decrease slightly with the increasing ZnF 2 content, but it is still approximate to that of ZBLAN glass (1.52).…”
Section: A Absorption Spectra and J-o Analysismentioning
confidence: 99%
“…An optical property of neodymium ions in several host matrices, such as glasses and ceramics, depends on their chemical composition and conditions of fabrication [8].…”
Section: Resultsmentioning
confidence: 99%